Concept Analysis of Web And Mobile Based Company Management Information System (Shopee E-Commerce Company Case Study) - Fauziah, Fenty (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2023)
This study aims to determine the application of the Management Information System used in organizing buying and selling activities at E-Commerce Shopee by analyzing the concept of various features contained in the Shopee application so that it can be implemented in a more systematic and structured manner. E-commerce is an act of buying and selling electronically using the internet as a medium, and Shopee is one of them. The research method used is descriptive and comparative methods, namely describing and comparing online and offline shopping on the Shopee application using the Wilcoxon test with 40 student respondents. The results showed that 0.001 means that it is smaller than 0.05, namely that there are differences in consumer use before and after using the Shopee application which implements a management information system that has an impact on consumer convenience in shopping.